INTERPRETASI DATA SEISMIK REFLEKSI : PICKING HORIZON DAN PICKING FAULT - Wibowo, Barrend Wellyadi; Hutagalung, Soly Deo Gloria (Pt. Anagata Sembagi Education, 2024)
Seismic method practicum has been carried out with the title